2007
DOI: 10.1111/j.1365-2982.2006.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the neurophysiological basis of chest wall allodynia induced by experimental oesophageal acidification – evidence of central sensitization1

Abstract: In somatic models of central sensitisation (CS) allodynia develops following changes to somatic A-beta fibres, allowing these afferents which normally only process innocuous sensations to encode pain. The aim of this study was to determine whether somatic allodynia induced by visceral sensitisation occurs via N-Methyl-D-Aspartate (NMDA) receptor mediated changes to the neurophysiological characteristics of somatic A-beta fibres. Twelve healthy subjects had oesophageal, chest wall and foot pain thresholds (PT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Acid stimulation has been used in several studies measuring electrical thresholds and 12-23% sensitization on group means has been measured using different methods and stimulation areas [28,42]. These results from previous studies stimulating high in the esophagus correspond well with those in the present study.…”
Section: Electrical Sensitization Potentialsupporting
confidence: 91%
“…Acid stimulation has been used in several studies measuring electrical thresholds and 12-23% sensitization on group means has been measured using different methods and stimulation areas [28,42]. These results from previous studies stimulating high in the esophagus correspond well with those in the present study.…”
Section: Electrical Sensitization Potentialsupporting
confidence: 91%
“…This results in A␤ fibers signaling to the sensitized region of the dorsal horn and innocuous stimuli being perceived as pain (37). We provided objective neurophysiological evidence to support this by recording somatosensory evoked potentials from the area of referred esophageal pain pre and postacid and showed that the amplitude of the somatosensory evoked potential increased and the latency decreased, demonstrating amplification of the large-diameter myelinated (A␤) fiber signaling pathway that is selectively activated at very low levels of electrical stimulation (34).…”
Section: Discussionmentioning
confidence: 92%
“…We have previously shown that esophageal acidification can induce somatic hypersensitivity and allodynia to electrical stimulation of the area or referred esophageal pain on the anterior chest wall (30,34). This somatic allodynia is thought to develop following esophageal tissue injury-induced central sensitization of spinal cord neurons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the studies on visceral hyperalgesia have demonstrated increased pain in response to one or more modalities after experimentally induced sensitization by chemicals (Sarkar et al, 2001(Sarkar et al, , 2003Drewes et al, 2003a;Hobson et al, 2004;Pedersen et al, 2004;Frøkjaer et al, 2005;Sami et al, 2006;Willert et al, 2007;Brock et al, 2009a).…”
Section: Visceramentioning
confidence: 99%